Planering av lägerområden : exemplet Sjöröd - Sandelius, Susanne (SLU/Dept. of Urban and Rural Development, 2008)
This is a final thesis on the landscape architecture program at the Swedish University of Agricultural Sciences. It is the end of five years of studies and comprises 30 ECTS.